Physiochemical and Microbiological Investigation of Surface and Ground Water Contaminants of Bhojpur Municipality - Gupta, Dipak Kumar; Bhandari, Dal Bahadur; Chaudhary, Prabhat Kumar; Yadav, Amar Prasad (Dristikon: A Multidisciplinary Journal, 2023)
Water is an essential resource for life evolution. 75% of the whole earth is covered by water. The water sources that flow through the social periphery represent the development and awareness of that society. This paper focuses on investigating contaminants of different water sources within Bhojpur Municipality. The six different water samples, based on their different latitudes, were collected following all the guidelines. The physiochemical parameters and microbiological organisms like E. Coli were tested and analyzed. The results revealed that the physiochemical parameters were mostly found to be within the guideline and standardization of the World Health Organization (WHO), but in the Silichung water sample, the number of bacteria was found to be out of the WHO limit. Physiochemical parameters like total dissolved solids (TDS), total solids (TS), and chloride content were not found under the guideline of WHO. The dissolved oxygen (DO) content was found more in the water sample of Bahundhara, whereas Bhandari well sample had a low amount of DO among the other samples. The biological oxygen demand (BOD) level in Sera Khola sample was found more, while Silichung sample had a low amount of BOD, indicating Sera Khola water sample is a bit more polluted than others. On microbiological testing, the Silichung water sample was tested with Providencia spp, indicating not useful for drinking purposes. Thus, it reveals that the Silichung water should not take directly, which is rich in Providencia spp. Other physiochemical parameters of other samples were found to be within the range of WHO.